Psalms 38 and 145 of the old Greek version - Gauthier, Randall X. (Vetus Testamentum, Supplements, 2014)
One of the critical, ongoing discussions in Septuagint Studies today concerns the issue of how texts were understood by their translators, and how those translations are able to provide the modern reader with clues to that original interpretation. In Psalms 38 and 145 of the Old Greek Version , Randall X. Gauthier provides a word by word, sentence by sentence, commentary on Psalms 38 and 145 in the Septuagint (LXX) version, or more accurately, the Old Greek (OG) version. Specifically, this study attempts to understand the semantic meaning of these psalms at the point of their inception, or composition, id est as translated literary units derivative of a presumed Semitic Vorlage .